Ogrody zoologiczne jako zakłady administracyjne - Duba, Mateusz (Studia Prawa Publicznego, 2025)
Posing the question of the position of zoological gardens within the systematics of administrative law allows for a deeper analysis and an attempt to classify them within the administrative legal system, focusing on their qualification as administrative establishments. Zoological gardens, which have been operating for over two hundred years, have undergone functional transformations, and today operate within the framework of nature conservation. Administrative law distinguishes nature protection as a core task of local and regional governments, with the administrative establishments they create serving to fulfill these tasks. The literature discusses issues related to defining administrative establishments and the difficulties involved in qualifying certain activities as public establishments. The blending of private and public law causes additional legal challenges. A particular difficulty for the doctrine lies in classifying or at least recognizing the existence of atypical administrative entities, whose essence is the performance of public tasks by non-public entities, under a specific concept developed within administrative law. The analysis conducted concludes that contemporary zoological gardens operate in several legal forms, the most common being the classical administrative establishment. Other legal forms, such as enterprises, foundations, and institutions, are also used. The most interesting and atypical form is what is termed a private-law public service establishment, which, as mentioned earlier, poses a challenge to the science of administrative law. The article concludes that the current state of affairs necessitates the introduction of new concepts. The analysis here facilitates conclusions regarding the doctrinal reform of the definition and typology of administrative establishments understood in the broad sense.